2016
DOI: 10.4103/2277-9531.184554
|View full text |Cite
|
Sign up to set email alerts
|

Implementing clinical governance in Isfahan hospitals: Barriers and solutions, 2014

Abstract: Introduction:In the new approach, all health care providers have been obligated to maintain and improve the quality and have been accountable for it. One of the ways is the implementation of clinical governance (CG). More accurate understanding of its challenges can help to improve its performance.Aims:In this study, barriers of CG implementation are investigated from the perspective of the hospitals involved. Besides, some solutions are suggested based on stakeholders’ opinions.Materials and Methods:This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…"It is cultured in the nursing system, but not in the medical system. It may be necessary to involve the head manager of medical departments in accreditation work" [12].…”
Section: Uncertainty About How To Participatementioning
confidence: 99%
See 1 more Smart Citation
“…"It is cultured in the nursing system, but not in the medical system. It may be necessary to involve the head manager of medical departments in accreditation work" [12].…”
Section: Uncertainty About How To Participatementioning
confidence: 99%
“…Physician training programs focus almost entirely on knowledge and skills for patients treatment and there is almost no training in health service management skills or effective quality improvement [11]. It is reported that many problems of physicians' non-participation can be solved by properly training them, creating appropriate motivation and facilitating their future participation [12]. The article by Mainz et al showed that physicians' resistance to quality assurance and quality improvement procedure and hospital accreditation is common in all countries and public health systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a structured, evidence-based tool, a portfolio shows the fulfillment of a profession’s standards for everyone practicing that career. It includes their vision of future growth and development [ 18 ] and provides the chance for capacity building in nursing continuous education [ 19 ] through reflecting on the practice and comparing the skills with the standards set by regulatory bodies. It offers the opportunity for self-assessment, identification of learning needs, and development of learning plans [ 20 ].…”
Section: Introductionmentioning
confidence: 99%